Towards Linking User Interface Translation Needs to Lexicographic Theory - du Plessis, André; Swart, Marius (Lexikos, 2015)
In a time of proliferating electronic devices such as smartphones, translators of user interfaces are faced with new challenges, such as the use of existing words in new contexts or in their obtaining new meanings. In this article, three lexicographic reference works available to translators in this field are compared: the Kuberwoordeboek/Cyber Dictionary (Viljoen 2006), the Pharos Afrikaans–Engels/English–Afrikaans Dictionary (Du Plessis et al. 2010) and the Microsoft Language Portal (www.microsoft.com/Language 2015). A list of selected examples (in English) is used to determine the extent to which each of these three works fulfils the needs of the user in terms of meaning discrimination for translating into Afrikaans. After determining this, an attempt is made to indicate whether the use of meaning discriminators such as part-of-speech markers, punctuation, paraphrases of meaning, and contextual and co-textual guidance (as indicated by Beyer 2009: 11) may have contributed to the success or failure of the given reference work, in order to arrive at a conclusion about the link between lexicographic theory and usability.